Study on the dehydration kinetics of tunellite using non-isothermal methods - Yilmaz, Muge Sari; Figen, Aysel Kanturk; Piskin, Sabriye (SPRINGER, 2015)
The thermal behavior of tunellite has been examined by using thermal analysis data at different heating rates. Coats-Redfern, Horowitz-Metzger, Piloyan-Novikova, Doyle, and isoconversional Ozawa kinetic models have been used for the non-isothermal dehydration kinetic investigation of the mineral. The kinetic parameters are computed using the above-mentioned models for all dehydration stages. In addition, structural characterizations of tunellite are analyzed by using an X-ray diffractometer, an inductive coupled plasma-optical emission spectroscopy, Fourier transform infrared spectroscopy, and a scanning electron microscope.
Keywords: Tunellite; Dehydration; Kinetic analysis; Isoconversional methods; Piloyan novikova; THERMAL-DECOMPOSITION; ULEXITE; Chemistry